2018
DOI: 10.5194/bg-15-809-2018
|View full text |Cite
|
Sign up to set email alerts
|

Virus-mediated transfer of nitrogen from heterotrophic bacteria to phytoplankton

Abstract: Abstract. Lytic infection of bacteria by viruses releases nutrients during cell lysis and stimulates the growth of primary producers, but the path by which these nutrients flow from lysates to primary producers has not been traced. This study examines the remineralisation of nitrogen (N) from Vibrio lysates by heterotrophic bacterioplankton and its transfer to primary producers. In laboratory trials, Vibrio sp. strain PWH3a was infected with a lytic virus (PWH3a-P1) and the resulting 36.0 µmol L −1 of dissolve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 47 publications
(63 reference statements)
3
8
0
Order By: Relevance
“…The accumulation of ammonium also corresponded to the utilization of organic matter. A previous incubation experiment also demonstrated that N-containing organic matter from vial lysates can be efficiently remineralized by heterotrophic bacteria, resulting in regenerated ammonium that could then be transferred to phytoplankton (Shelford & Suttle, 2018). In present study, ammo- (Shelford & Suttle, 2018).…”
Section: Viral Lysis Within the Aquatic Microbial Food Websupporting
confidence: 57%
“…The accumulation of ammonium also corresponded to the utilization of organic matter. A previous incubation experiment also demonstrated that N-containing organic matter from vial lysates can be efficiently remineralized by heterotrophic bacteria, resulting in regenerated ammonium that could then be transferred to phytoplankton (Shelford & Suttle, 2018). In present study, ammo- (Shelford & Suttle, 2018).…”
Section: Viral Lysis Within the Aquatic Microbial Food Websupporting
confidence: 57%
“…It has also been reported that viruses from different stages of infection are released from host bacterial cells at the same time, which can cause a large increase for the VBR value (Siokou-Frangou et al, 2010). Viruses can stimulate the growth of bacteria, and there are close relationships between viruses and bacteria, which has been supported by the results of many studies (Shelford and Suttle, 2018;Bongiorni et al, 2005;Stroinov et al, 2011;Vrede et al, 2003). In our study, we found that the abundance of viruses was positively related to abundance of bacteria.…”
Section: Correlation Between Virus and Bacteriasupporting
confidence: 85%
“…HOT4B5, which inhibits the growth of Prochlorococcus MIT9313 (Sher et al ., 2011). An alternative explanation is that host lysis by viruses releases nutrients and stimulates the growth of uninfected hosts, including cyanobacteria and heterotrophic bacteria (Sher et al ., 2011; Shelford and Suttle, 2018).…”
Section: Discussionmentioning
confidence: 99%